THE INFLUENCE OF FINE ARTS ON HUMAN PSYCHOLOGY - Moxigul Mamataliyeva (Bright Mind Publishing, 2025)
This article examines the impact of visual arts on human psychology. The article analyzes how visual arts interact with individual and social psychological factors, the reception of works of art and its impact on our emotional experiences. It examines how visual arts can be used for psychotherapeutic and pedagogical purposes, as well as the role of art in direct emotional, cognitive and social development. The article also analyzes the existing scientific literature on the psychological and emotional impact of works of art, and from a scientific perspective sheds light on how visual arts affect the human brain and mental state.
Keywords: Visual arts, human psychology, psychotherapy, cognitive development, emotional impact, art and pedagogy, psychological analysis, reception of works of art, emotional development, art and mental state.